2015
DOI: 10.4172/2161-0983.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Bed Bugs Epidemic in the United States

Abstract: Studies and reports suggested that bed bug infestation has been increasing rapidly in the United States since 2004. Scientists suggested that the reason for this resurgence of bed bugs is the less use of pesticides and the international immigration where foreign people carry bed bugs with them into the country. The main purpose of this review is to study the causes of the rapid bed bugs' infestation and its effect on human health. It will also discuss the best ways to control this epidemic. This review article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…As it was showed outdoor temperature can play important role in determination of the bed bug infestation season. Alalawi found that bed bug infestation season reaches its peak in August and September, while in January and February, the lowest infestation rate of bed bugs in a year is recorded in the United States (28). Similarly, Mabud et al also detected prominent seasonality in bed bug reporting, peaking in August and reaching a nadir in February each year (29).…”
Section: Table 2 Standard Deviation (Sd) Standardized (B) and Unstamentioning
confidence: 93%
“…As it was showed outdoor temperature can play important role in determination of the bed bug infestation season. Alalawi found that bed bug infestation season reaches its peak in August and September, while in January and February, the lowest infestation rate of bed bugs in a year is recorded in the United States (28). Similarly, Mabud et al also detected prominent seasonality in bed bug reporting, peaking in August and reaching a nadir in February each year (29).…”
Section: Table 2 Standard Deviation (Sd) Standardized (B) and Unstamentioning
confidence: 93%